Perforated acute abdomen in a patient with COVID-19: an atypical manifestation of the disease - Corrêa Neto,Isaac José Felippe (2020)
Abstract Introduction: The Coronavirus belongs to a family of RNA viruses that can cause respiratory infection, with the possibility of gastrointestinal manifestations in approximately 5-50% of the cases. Objective: To report a surgical case with a diagnosis of COVID-19 that developed acute perforated abdomen and pneumothorax. Case report: This was an 80-year-old female patient with respiratory symptoms, with dry cough and fever and diffuse abdominal pain with signs of peritonitis. She had leukocytosis, kidney dysfunction and an increase in D-dimer with positive PCR for COVID. Computed tomography of the chest and abdomen showed pneumothorax on the right and extensive pneumoperitoneum. Conclusion: The presentation of COVID-19 with severe pulmonary and abdominal complications requires specialized and emergency treatments, but it has high mortality rates.